Attitude and Needs Toward MTM Applications of Chronic Disease in China: A Questionnaire Survey - Huang, Shiqiong; Huang, Juanjuan; Deng, Xuanyu; Ouyang, Lihui; He, Gefei; Sun, Ji (Frontiers in Public Health, 2022)
Objective: Chronic diseases are characterized by high incidence, long-term medication and complex types of medication. There are also many corresponding medication therapy management (MTM) applications on the market, such as iCarea, Medisafe. However, the existing research mainly focuses on how to choose high-quality MTM applications, and few researches considers the expectations of MTM applications from potential users. The aims of this study were to investigate the demand, attitude and expectations of the Chinese patients for the MTM applications to support. Methods: From August 2019 to December 2019, we created a questionnaire to have knowledge of user needs, preferences and expectations for MTM applications among 302 chronic patients in Hunan, Guangdong and other provinces in China. Logistic regression analysis was performed to analyze the risk factors of affecting patients’ attitude towards MTM applications. Then, respondents’ expectations and preferences for MTM applications were statistically analyzed. The survey data were merged to provide information for the design of targeted chronic disease MTM applications. Results: A total of 260 (86.09%) out of 302 patients the respondents were willing to use the MTM applications of chronic disease. The independent influencing factors for using the MTM applications were long-term medication history (OR=4.45, P<0.001), willing to learn about medicine knowledge (OR=3.01, P=0.04), and wanting to get more professional medication knowledge via Internet (OR=2.86, P=0.005). It was worth noting that among those willing to use MTM applications, 55.00% of respondents were willing to use WeChat applet for MTM, while only 23.46% of respondents preferred other applications. As to more prevalent WeChat applet for MTM, the majority of participants expected the inclusion of useful modules such as medication log (62.81%), medication reminder (62.81%) and medication recommendations (57.79%). Conclusion: The participants are willing to use MTM applications of chronic disease, with a preference of WeChat applet. Patients tended to use MTM applications if they had a long-term medication history or a desire for medical knowledge, especially if they want to get more professional medication knowledge via Internet. Participants are more expected to include in WeChat applet as medication log, medication reminder and medication recommendations.